2020
DOI: 10.1021/acsomega.0c04436
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Affinity Sensor Based on a Molecularly Imprinted Polymer for Ultrasensitive Detection of Chlorpyrifos

Abstract: The persistent use of pesticides in the agriculture field remains a serious issue related to public health. In the present work, molecularly imprinted polymer thin films were developed using electropolymerization of pyrrole (py) onto gold microelectrodes followed by electrodeposition for the selective detection of chlorpyrifos (CPF). The molecularly imprinted polymer (MIP) was synthesized by the electrochemical deposition method, which allowed in-line transfer of MIP on gold microelectrodes without using any a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…The static adsorption experiments (Figure B) showed that the adsorption of CPF by both MMMIP and NIPs increased with the increase of the initial concentration, and MMMIP showed a superior adsorption performance to NIPs. In addition, compared with the previously reports on the adsorption of CPF by MIPs, the MMMIP synthesized by this method has a higher adsorption performance on CPF, ,, which has potential application in the enrichment and separation of trace CPF in complex matrices.…”
Section: Resultsmentioning
confidence: 82%
“…The static adsorption experiments (Figure B) showed that the adsorption of CPF by both MMMIP and NIPs increased with the increase of the initial concentration, and MMMIP showed a superior adsorption performance to NIPs. In addition, compared with the previously reports on the adsorption of CPF by MIPs, the MMMIP synthesized by this method has a higher adsorption performance on CPF, ,, which has potential application in the enrichment and separation of trace CPF in complex matrices.…”
Section: Resultsmentioning
confidence: 82%
“…This is a consequence of CPF rebinding at the cavities in the PPy matrix, which primarily occurs via hydrogen bonding between the N group of pyridine in CPF and the N−H group of PPy. Recovery from spiked cucumber and pomegranate ranged from 91 to 97% with an RSD of 5% [117].…”
Section: Insecticidesmentioning
confidence: 99%
“…Electrochemical transduction has usually been in use in biosensor design because of its high degree of sensitivity, LoD and selectivity within a wide detection range [ 7 , 8 , 9 , 10 , 11 ]. Such transduction strategies are extremely suitable for integration with flexible electrodes, and as such, have proved immensely beneficial in the point-of-care scenario [ 12 ].…”
Section: Introductionmentioning
confidence: 99%